Adoption at Dr. Kariadi Hospital Semarang - Soetadji N.; Moeljono S. Trastotenojo; R. Harijono; Soerarjo Darsono; Siti Alfinah; Djoko Waspodo (Indonesian Pediatric Society, 1976)
Procedures and other arrangements concerning adoption at Dr. Kariadi Hospital, Semarang, is discussed in this paper. From 1969 to the first three months of 1974, 41 children with ages ranging between 5 days and 3 years old have been adopted. A visit to 18 of them showed that their health condition was satisfactory; a psychological evaluation also indicated that no mental retardation was observed, excepting that their I.Q. level was difficult to determine. Five children received official approval from the court, one from the notary and the others from the local District Head (Lurah/Camat).